C++ and Java performance on the Android platform - Wlazło, Paweł; Smołka, Jakub (Journal of Computer Sciences Institute, 2022)
The article presents a comparative analysis of Java and C ++ technologies in terms of performance on the Android platform. The research was carried out on custom applications in both languages. The series of repetitions of each test were performed on three research units - Samsung and Xiaomi devices. The following criteria were used: test execution time, CPU load, and RAM usage. The performance, in most of the carried out tests, was in favor of the C++ language, and the main difference and with the greatest discrepancy between the technologies tested was the execution time, where C++ scored 18 points, and Java only 3 points. For the CPU usage, the result was the same, but value differences were much smaller. A nondiscerning parameter that was the use of RAM. C++ received 11 points and Java 10.